PENGARUH KAPASITAS INTELEGENSI MELALUI MENYIMAK DAN MEMBACA TERHADAP PRESTASI BELAJAR SISWA SMAN DI KOTA BANDUNG - adiwiria, pien supinah (LITERA, 2008)
AbstractThis research study aims to investigate the direct effect of the intelligence capacity on learning achievement and the indirect effect of the intelligence capacity on learning achievement through listening and reading. This study employed the explanatory survey design. The sample, consisting of 112 students of SMAN in Bandung City, was selected by using the multi-stage cluster sampling technique. The research instruments were tests. The statistical test employed was the path analysis. The research findings show that the intelligence capacity has a direct effect on learning achievement and an indirect effect on learning achievement through listening and reading. The intelligence capacity will have a greater effect on learning achievement if it is supported by the reading ability. The effect of the intelligence capacity on learning achievement through listening is smaller than the direct effect of the intelligence capacity on learning achievement.Key words: intelligence capacity, listening ability, reading ability, learning achievement